(untitled) (Journal Of Educational and Psychological Researches, 2025)
The research aims to measure moderation among graduate students. The research sample consisted of 372 male and female postgraduate students, who were selected randomly from the scientific and humanitarian faculties for the academic year 2022-2023. The researcher used the mood moderation scale in its final form, which included 26 items. The researcher used the statistical package for the social sciences (SPSS) in analyzing and extracting the data, which is a t-test for one sample. The results showed that the research sample has a good level of mood moderation.